An Analysis of How Relationship Marketing Influences Customer Choice of Hotel Industry - Pathmananathan, P. Ravindran; Aseh, Khairi (Archives of Business Research, 2021)
Relationship marketing has been recognised as an excellent way to build an exclusive long-term relationship with their customers in today's dynamic global industry.However, many institutions fail to systematically gauge and track customer satisfaction and the factors shaping it. An increasing number of institutions are making customer satisfaction a main concern. The aim of this study is to highlight the importance of customer satisfaction in the service industry.This study was carried out via a questionnaire involving 200 customers of hotel located in urban areas namely, Georgetown, Penang. It can be concluded that there is a positive relationship between customer satisfaction and customer retention. Thus,the higher the level of customer satisfaction the higher the likelihood a customer will repeat staying at the hotel and recommend hotels to others.